The 2008 Sichuan Earthquake and Its Impacts on Economy - Tareen, Hashmatullah (European Scientific Journal, ESJ, 2023)
China, with one of the largest populations and the second-largest gross domestic product (GDP), experiences severe earthquake disasters. The Great Sichuan earthquake, one of the deadliest in Chinese history and the most devastating in China since the 1980s, occurred in 2008. This earthquake is characterized by its massive damage to the economy and the loss of a huge number of human lives. This study primarily focused on summarizing the existing studies related to the economic impacts of the Sichuan earthquake and specifically sought to identify the impacts of the Sichuan earthquake on the economy in the affected area. As a result, the earthquake had a significant long-term negative impact on the overall GDP. The earthquake greatly affected the tourist industry, and it has destructively influenced the development of the tourism industry in the quake-hit area. Also, this earthquake harmed the agricultural output in the damaged areas with different magnitudes in the Sichuan province. In addition, the Sichuan earthquake caused extensive damage to local critical infrastructure. The results implied that agricultural, tourism, and infrastructure inputs were reduced in the affected areas. Finally, it could serve as an important reference for the development program after a major earthquake.